Introduction to data base management in business - Bradley, James (New York : Holt, Rinehart, and Winston, 1983)
This book is designed for self study, it covers the full spectrum of the subject of database management system.
Includes bibliographical references and.index
ijb 16/01/2019
Loans
Keywords: Business; Database management